An Analytical Study of the Electoral Performance of Pakistan’s Religious Political Parties in the General Election of 2024 - Muhammad Umeir Aslam; Mohamad Zaidi bin Abdul Rahman; Raja Hisyamudin bin Raja Sulong (Journal of Islamic Thought and Civilization, 2026)
This study presents an analytical review of the electoral performance (EP) of religious political parties (RPPs) in Pakistan's 2024 general elections (GE). Despite a strong ideological background, prominent religious parties such as Jamaat-e-Islami (JI), Jamiat Ulema-e-Islam (JUI), Tehreek-e-Labbaik Pakistan (TLP), and Jamiat Ulema-e-Pakistan (JUP) were unable to demonstrate effective national-level EP in this election. Only JUI and Majlis Wahdat-e-Muslimeen (MWM) managed to secure five seats. The study was conducted using a mixed methods approach, based on official electoral results, party manifestos, media reports, and scholarly analyses. According to the research, the reasons for the poor EP of religious parties include lack of unity among them, outdated and ineffective narratives, limited financial resources, weak electoral campaigns, and a declining trend of voting on religious grounds among voters. Furthermore, electoral fraud, political instability, administrative weaknesses, and media restrictions also impacted their performance. The findings indicate that unless religious parties implement fundamental reforms in their narratives, electoral strategies, and organizational coordination, they will gradually become ineffective in Pakistan's evolving democratic landscape. In this context, it is essential for them to focus on public issues and align with contemporary political requirements to regain public trust.